State violence, collusion and the Troubles : counter insurgency, government deviance and Northern Ireland - Punch, Maurice (Pluto Press ; Distributed in the United States exclusively by Palgrave Macmillan, 2012)
"This is the story of how the British state collaborated with violent groups and directly participated in illegal violence. It also raises urgent questions about why states around the world continue to deploy such violence rather than seeking durable political settlements."--Page 4 of cover